Tax Policy, Leverage and Macroeconomic Stability. (Policy Papers; Policy Paper ;, 2016)
Risks to macroeconomic stability posed by excessive private leverage are significantly amplified by tax distortions. 'Debt bias' (tax provisions favoring finance by debt rather than equity) has increased leverage in both the household and corporate sectors, and is now widely recognized as a significant macroeconomic concern. This paper presents new evidence of the extent of debt bias, including estimates for banks and non-bank financial institutions both before and after the global financial crisis. It presents policy options to alleviate debt bias, and assesses their effectiveness. The paper finds that thin capitalization rules restricting interest deductibility have only partially been able to address debt bias, but that an allowance for corporate equity has generally proved effective. The paper concludes that debt bias should feature prominently in countries' tax reform plans in the coming years.